Development of Community Agricultural Tourism by Multilateral Organization in Wang-Yang Community, Suphan Buri Province - Khamkerd, Thong; Chaiyo, Palarak; Sangiemsilp, Piengruthai; Therawat, Jittraporn; Rueangrit, Uthumporn; Chuayphen, Phornthip (Area Based Development Research Journal, 2020)
This study has an objective to develop the community agricultural tourism by a multilateral organization in Wang Yang community, Si Prachan district, Suphan Buri province. This study is participatory action research. Network partners are tourist communities in Si Prachan district, government, private sector, academic sector and local administrative offices. Processes used in this study are 1) the development of community agricultural tourism by a multilateral organization, 2) the development of a community agricultural tourism program, 3) the driving mechanism of multilateral agricultural tourism, 4) the development of a community agricultural tourism management system, 5) knowledge sharing among communities, 6) work efficiency evaluation, 7) mutual lessons learned, and 8) knowledge transfer to practical application. The study results in 1) local people having a better quality of life, 2) the project included in the Local Development Plan B.E. 2018-2022 of Wang Yang Subdistrict Municipality, 3) the 1st Water Chestnut Food Festival, and 4) integration of a community agricultural tourism development plan by a multilateral organization, which creates the tourism connection to a provincial scale and a sustainable change in the area. The income of the community then increases by 32%. In conclusion, a mechanism of a robust multilateral organization for developing the agricultural tourism in Si Prachan district has been initiated, generating a better quality of life, community strength, and income distribution based on the community resource sustainably.